Husband Support and Maternal Mental Health Among Pregnant Women in Independent Midwifery Practices - Damai Yanti Simanjuntak; Karwati Karwati; Sri Maryati (Ahmar Metastasis Health Journal, 2026)
Evidence on the role of husband support in maternal mental health remains limited in community-based midwifery services in Indonesia. This study aimed to examine the relationship between husband support and maternal mental health among pregnant women attending independent midwifery practices in Cimahi City and to explore the psychosocial mechanisms underlying this relationship. A convergent mixed-methods design was employed, involving 72 pregnant women for the quantitative component and 20 participants for in-depth qualitative interviews. Husband support, antenatal anxiety, and emotional wellbeing were assessed using validated questionnaires. Quantitative data were analyzed using Pearson correlation and multiple linear regression, while qualitative data were examined through thematic analysis. Husband support was significantly associated with lower antenatal anxiety and higher emotional wellbeing and remained an independent predictor of maternal mental health after controlling for maternal age, education, parity, and economic status. Descriptive findings indicated that a considerable proportion of participants experienced moderate to severe antenatal anxiety. Qualitative analysis identified emotional presence, shared responsibility, and affirmation of maternal identity as key mechanisms through which husband support strengthened maternal coping capacity. These findings demonstrate that husband support serves as an important protective psychosocial factor for maternal mental health. Integrating family empowerment strategies into routine antenatal care may improve psychological wellbeing and strengthen community-based maternal health services.